2016
DOI: 10.1016/j.arthro.2015.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Adipose-Derived Regenerative Cells Promote Tendon-Bone Healing in a Rabbit Model

Abstract: 4 5Purpose: To evaluate the therapeutic effect of adipose-derived regenerative cell (ADRC) 6 administration on tendon-bone healing in a rabbit ACL reconstruction model. 7Methods: Anterior cruciate ligament (ACL) reconstruction with semitendinosus tendon autograft 8 was performed on the right knees of adult white rabbits. Eighty rabbits were divided into 2 groups: 9 a treatment group, in which the graft was coated with ADRCs mixed in fibrin glue carrier during 10 surgery, and a control group, in which the graft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 30 publications
(2 reference statements)
1
36
1
Order By: Relevance
“…UADSCs were isolated by a previously established method . Adipose tissues (1.5 g) of male rabbits were harvested from the adipose tissue pouch in the interscapular region located along the dorsomedial line, nearly 5 cm from the skull in the craniocaudal direction.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…UADSCs were isolated by a previously established method . Adipose tissues (1.5 g) of male rabbits were harvested from the adipose tissue pouch in the interscapular region located along the dorsomedial line, nearly 5 cm from the skull in the craniocaudal direction.…”
Section: Methodsmentioning
confidence: 99%
“…UADSCs were isolated by a previously established method. 14,25 Adipose tissues (1.5 g) of male rabbits were harvested from the adipose tissue pouch in the interscapular region located along the dorsomedial line, nearly 5 cm from the skull in the craniocaudal direction. Subsequently, the tissue was washed with phosphate-buffered saline (PBS) solution (Wako, Osaka, Japan) and cut into strips over a period of 5 min.…”
Section: Uadscs Preparationmentioning
confidence: 99%
“…Efforts for this type of augmentation include the use of fibrin clots, platelet-rich plasma, synthetic scaffolds, and stem cells in the effort to increase localized production of beneficial growth factors. [4][5][6][7][8][9] Fibrin clots can be formed from peripheral blood and comprise a fibrin meshwork that can capture and contain platelets, act as a reservoir for cells, growth factors, and other bioactive factors, and provide an effective delivery system for cells. 10,11 Fibrin clots have been shown to enhance the surgical repair of tissue with poor healing capacity.…”
mentioning
confidence: 99%
“…Previous research using ADRC in ACL reconstruction has mainly involved animal studies. [29][30][31] Teuschl et al compared the degradation and regeneration potential (ligamentization) of ACL reconstruction with degradable silk fiber-based scaffold with or without ADRC in sheep. 29 Despite the authors observed better histological characteristics 6 months after surgery in the cell-seeded scaffold, there were no significant between-group differences in silk fiber degradation and tissue regeneration at 12 months.…”
Section: Discussionmentioning
confidence: 99%